Application of the Principle of Portability for Participants of National Health Insurance outside the Domicile Area in Gaining Access to Health Services in the City of Semarang - Marni Dominika Oenunu; Yohanes Budi Sarwo; Daniel B. Wibowo; Endang Wahyati Yustina (SOEPRA, 2021)
Abstract: The portability principles in the National Health Insurance Program (JKN) implementation are principles that guarantee JKN participants whenever and wherever they are as far as in the Indonesian area. This includes any participant who moves his/her job or residence, has a vacation, does a study or does other business. This happens in all areas in Indonesia, including in Semarang City. The philosophical base for the implementation of the portability principle is the right to access health services. When suffering sick a JKN participant should receive his or her health insurance rights by possibly accessing health services at the nearest degree of First Level Health Facility. However, the fact was that remained facing obstacles. The purpose of this study was to obtain an overview of the form regulations, the factors influencing the implementation of portability principles for out-domiciled JKN participants in getting access to health services at Semarang City. This study used a socio-legal approach having a descriptive-analytical specification. The primary data of this study were obtained through interviews with the Health Social Security Organizing Agency (BPJS) of Semarang Branch and five health centre’s heads, namely Pandanaran, Sekaran, Ngesrep, Srondol, and Kedungmundu health centres beside 25 out-domiciled JKN participants of Semarang as informants. The sampling technique used purposive sampling with qualitative analysis. The implementation of the portability principles for out-domiciled JKN participants in getting access to health services at Semarang City, especially in the 5 health centres does not go well. The form regulations of the implementation portability principles based on a circular letter issued by Health BPJS Office of Semarang Branch number 766 / VI-01/0518 on Out-Domiciled Participant Services of FKTP is maximum visit limit 3 times which is contrary to the portability principles in Article 4 of Act No. 40 of 2004 on National Social Security System and Act No. 24 of 2011 on the Social Security Organizing Agency. Need for technical regulations in the form of a binding Minister Decree concerning requirements, administrative procedures, and service procedures for the implementation of portability principles. Juridical factors influencing were there are no technical regulations on the implementation of the portability principles for out-domiciled JKN participants in getting access to health services including the utilization of the JKN Mobile application. Social factors and technical factors had no adequate information and understanding to implement the portability principles. Keywords: principles portability, JKN, domicile, services. Abstrak: Prinsip portabilitas dalam penyelenggaraan Program Jaminan Kesehatan Nasional (JKN) merupakan prinsip menjamin peserta JKN kapan dan dimanapun di Indonesia termasuk saat berpindah pekerjaan atau tempat tinggal, liburan, kuliah atau urusan lainnya tak terkecuali di Kota Semarang. Landasan filosofis penerapan prinsip portabilitas adalah hak akses pelayanan kesehatan. Peserta JKN ketika sakit seharusnya memperoleh hak akses pelayanan kesehatan di Fasilitas Kesehatan Tingkat Pertama (FKTP) terdekat, namun faktanya masih ditemui kendala. Tujuan penelitian adalah untuk mendapatkan gambaran bentuk pengaturan, faktor-faktor yang mempengaruhi dan penerapan prinsip portabilitas bagi peserta JKN di luar wilayah domisili dalam memperoleh akses pelayanan kesehatan di Kota Semarang.Metode penelitian yang digunakan adalah pendekatan yuridis sosiologis dengan spesifikasi penelitian deskriptif analitis. Data primer diperoleh melalui wawancara dengan Badan Penyelenggaraan Jaminan Sosial (BPJS) Kesehatan Kantor Cabang Semarang dan lima Kepala Puskesmas: Pandanaran, Sekaran, Ngesrep, Srondol, dan Kedungmundu sebagai narasumber serta 25 responden peserta JKN luar wilayah domisili Kota Semarang. Metode sampling menggunakan purposive sampling dengan analisis kualitatif.Penerapan prinsip portabilitas bagi peserta JKN di luar wilayah domisili dalam memperoleh akses pelayanan kesehatan di Kota Semarang terutama di kelima Puskesmas yang diteliti belum optimal. Bentuk pengaturan penerapan prinsip portabilitas didasarkan Surat Edaran BPJS Kesehatan Kantor Cabang Semarang Nomor 766/VI-01/0518 tentang Pelayanan Peserta Peserta Luar Wilayah di FKTP yaitu batasan maksimal kunjungan 3 kali yang bertentangan dengan prinsip portabilitas dalam Pasal 4 huruf f Undang-Undang Nomor 40 Tahun 2004 tentang SJSN dan Undang-Undang Nomor 24 Tahun 2011 tentang BPJS. Perlu peraturan teknis berupa Keputusan Menteri yang mengikat tentang persyaratan, prosedur administratif, dan prosedur layanan penerapan prinsip portabiltas tersebut. Faktor yuridis yang mempengaruhi yaitu belum ada peraturan teknis tentang penerapan prinsip portabilitas bagi peserta JKN di luar wilayah domisili dalam memperoleh akses pelayanan kesehatan termasuk pemanfaatan aplikasi Mobile JKN. Faktor sosial dan faktor teknis juga masih kurang informasi dan pemahaman dalam penerapannya.Kata kunci: prinsip portabilitas, JKN, domisili, pelayanan.